2021
DOI: 10.1002/adem.202100535
|View full text |Cite
|
Sign up to set email alerts
|

SiOC(N) Cellular Structures with Dense Struts by Integrating Fused Filament Fabrication 3D Printing with Polymer‐Derived Ceramics

Abstract: Great advances have been made in various 3D printing methods for ceramics. Fabrication of Si‐based ceramics using polymer‐derived ceramics (PDCs) is gaining popularity. Using this route, preceramic polymers can be shaped in the polymer state and then pyrolyzed to produce different types of ceramics. Cellular ceramics can be manufactured using this technique. Herein, the novel fabrication of cellular ceramics with a two‐step process using PDCs is reported. First cellular structures are 3D printed with fused fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 80 publications
0
14
0
Order By: Relevance
“…The research also showed that the scaffolds can be manufactured, with high reproducibility and industrial tolerances, at an affordable and thus accessible price. The preliminary biological studies proved the material to be non-cytotoxic, promote fast cell adhesion, and early-stage cell activations [43]. In the present study, the research is focused on the impact of the geometry of the scaffold on the osteogenic differentiation of hMSCs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The research also showed that the scaffolds can be manufactured, with high reproducibility and industrial tolerances, at an affordable and thus accessible price. The preliminary biological studies proved the material to be non-cytotoxic, promote fast cell adhesion, and early-stage cell activations [43]. In the present study, the research is focused on the impact of the geometry of the scaffold on the osteogenic differentiation of hMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the materials used as well as the geometry of the scaffold have relevant impacts on the biological performance. In our previous study [43] the fabrication procedures were optimized and the physical, mechanical, chemical, and preliminary biological properties of the SiOC(N) ceramic scaffolds were already thoroughly characterized. The results demonstrated that the novel method eliminates the possibility of having pores or defects inside the struts with complete impregnation of the preceramic polymer in the TPU structures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A novel method of fabricating SiOC(N) cellular structures with dense struts by integrating FFF 3D printing with polymer-derived ceramics was reported in our previous paper. The method utilizes the simplicity of the polymer FFF combined with the polymer-derived ceramics to obtain high-resolution ceramic scaffolds [40,41] with both tunable pore size and low-cost fabrication on a RepRap-class 3D printer able to print thermoplastic elastomer [42,43]. Moreover, the preliminary biological evaluations in a previous study showed that the ceramic material has good cytocompatibility, promoting fast cell adhesion and early-stage cell activities [40].…”
Section: Introductionmentioning
confidence: 99%